When Families Become Perpetrators: A Case Series on Familial Trafficking - White, C. Nicole (Journal of family violence, 2024)
PurposeHuman trafficking occurs when a person uses force, fraud, or coercion to obtain an act or service from another person. While trafficking is often depicted as a crime perpetrated by strangers, recent literature has found family members can also be traffickers. Only four peer reviewed studies have specifically examined familial trafficking.MethodThe current study builds upon this sparse literature by reviewing medical charts of patients in a large hospital system who were identified as survivors of familial trafficking between October 2017 and September 2021. Descriptive statistics are reported for all 39 identified patients.ResultsMajority of patients were female (92.3%) and under 36 years old (56.4%; M = 34.2, SD = 11.6). Despite most patients now being adults, all except one were minors at the time the trafficking began. Parents were the most common perpetrator (66.7%) followed by aunt/uncle (12.8%). Nine cases were chosen, given level of detail in patient charts, to be highlighted in a case series to further describe the experiences of these survivors. Cases examined included labor trafficking, parents as perpetrators, intersection of substance use, and males as victims. Force was the most common means of control used and often manifested as physical or sexual abuse that preceded the exploitation. Another reoccurring theme was substance use being a factor when parents were perpetrators.ConclusionThe findings from this paper can help inform screening techniques by encouraging providers to inquire about familial relationships. Findings may also be helpful for providers working with this population and future research endeavors.